2003
DOI: 10.1080/00071660310005198319
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of artificially incubated Greater Rhea (Rhea americana) eggs

Abstract: 1. This paper is a report of biological agents that contaminate Greater Rhea (Rhea americana) eggs during artificial incubation. 2. The cleanliness of eggs when collected, and the period of storage prior to incubation, were investigated to assess their effects on microbial contamination and hatchability. 3. A total of 14 bacteria and 4 fungi species were isolated within the egg in the laboratory. 4. Microbial contamination was higher (24%) in very dirty eggs than in eggs which were clean or dirty (16%). Hatchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The slight delay of the date of laying onset (9 d) in the Aliba® group with respect to the control group might be attributed to the change in the food type made one month before the date of the laying onset reported in the literature (Lábaque et al, 2003(Lábaque et al, , 2004(Lábaque et al, , 2010Martella and Navarro, 2006). Hence, these individuals might have gone through a period of neophobia to the novel food (Marples and Kelly, 1999).…”
Section: Discussionmentioning
confidence: 75%
“…The slight delay of the date of laying onset (9 d) in the Aliba® group with respect to the control group might be attributed to the change in the food type made one month before the date of the laying onset reported in the literature (Lábaque et al, 2003(Lábaque et al, , 2004(Lábaque et al, , 2010Martella and Navarro, 2006). Hence, these individuals might have gone through a period of neophobia to the novel food (Marples and Kelly, 1999).…”
Section: Discussionmentioning
confidence: 75%
“…Studies carried out so far have focused mainly on bacteria, primarily of the genus Salmonella (BRUCE & DRYSDALE 1983;CASON et al 1994;COX et al 2000;GAST et al 2005;KIZERWETTER-OEWIDA & BINEK 2008). However, only a few studies have investigated the contamination of hatching bird eggs with microscopic fungi and their impact on embryogenesis (LÁBAQUE et al 2003;GIGLI et al 2009;NOWA-CZEWSKI et al 2011). It was shown that the consequence of the presence of microscopic fungi in the egg is embryo mycosis.…”
mentioning
confidence: 99%
“…and Cryptococcus spp. have been identified in the normal microbiota of the oropharynges and cloacae of ostriches (Cooper et al, 2009;Lábaque et al, 2003;Evans et al, 2004). While attempting to isolate filamentous fungi from the oropharynges and feces of ostriches obtained negative results; however, possible cases of pulmonary infection by these agents should be considered because their lower respiratory tracts are particularly affected by the inhalation of propagules present in the environment.…”
Section: Discussionmentioning
confidence: 99%